2009
DOI: 10.1111/j.1365-2036.2008.03919.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and complications of adalimumab treatment for medically‐refractory Crohn’s disease: analysis of nationwide experience in Scotland (2004–2008)

Abstract: SUMMARY BackgroundAdalimumab is a second generation humanized anti-tumour necrosis factor (TNF) monoclonal antibody with established efficacy in Crohn's disease (CD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 30 publications
7
58
1
1
Order By: Relevance
“…Previous studies have demonstrated the efficacy of antitumour necrosis factor-alpha (anti-TNF-a) agents (including infliximab and adalimumab) in patients with Crohn's disease (CD) [1][2][3][4] ; and thus infliximab has shown efficacy in the short-term treatment of refractory luminal and fistulising CD, 4,5 and also efficacy in a more longterm perspective. 1,[6][7][8] Since a number of patients will, however, require surgery after having anti-TNF-a agent therapy in the recent past, the surgeons will, therefore, be increasingly faced with abdominal surgery on CD patients with suppressed immune response in the preoperative setting and consequently concerns about an increased risk of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated the efficacy of antitumour necrosis factor-alpha (anti-TNF-a) agents (including infliximab and adalimumab) in patients with Crohn's disease (CD) [1][2][3][4] ; and thus infliximab has shown efficacy in the short-term treatment of refractory luminal and fistulising CD, 4,5 and also efficacy in a more longterm perspective. 1,[6][7][8] Since a number of patients will, however, require surgery after having anti-TNF-a agent therapy in the recent past, the surgeons will, therefore, be increasingly faced with abdominal surgery on CD patients with suppressed immune response in the preoperative setting and consequently concerns about an increased risk of post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, rituximab, a novel monoclonal antibody agent used as a therapeutic option to deplete B-lymphocyte populations, was used to reportedly treat multiple distal ileal perforations in a patient with Wegener's granulomatosis [66] . A number of reports, noted above, have also recorded rare cases of free perforation in CD following anti-tumor necrosis factor (TNF) monoclonal antibody treatment [15][16][17] . Cases treated with either infliximab or adalimumab have been documented [15][16][17] .…”
Section: Medication-related Causesmentioning
confidence: 99%
“…A number of reports, noted above, have also recorded rare cases of free perforation in CD following anti-tumor necrosis factor (TNF) monoclonal antibody treatment [15][16][17] . Cases treated with either infliximab or adalimumab have been documented [15][16][17] . In one patient, free perforation developed after the initial dose of infliximab [16] .…”
Section: Medication-related Causesmentioning
confidence: 99%
See 2 more Smart Citations